2018
DOI: 10.1002/ps.4881
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs of infection with Serratia symbiotica are associated with greater susceptibility to insecticides in the pea aphid Acyrthosiphon pisum

Abstract: Our study demonstrates that S. symbiotica plays an important role in the ability of aphid hosts to tolerate insecticides. These results provide insight into the potential changes in tolerance to insecticides in the field because there is a continuous and dynamic process of symbiont acquisition and loss that may directly affect host biology. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 76 publications
(210 reference statements)
6
76
3
1
Order By: Relevance
“…Our results demonstrated that, once in the gut, cultivable S. symbiotica infections have negative effects on some A. fabae host life history traits in the absence of environmental stressors. These effects are similar to those found in previous studies that emphasize the costs associated with the presence of facultative endosymbionts for aphids, including the defensive endosymbiont Hamiltonella defensa (23,(27)(28)(29)(30)48). There may be several potential causes of virulence of cultivable S. symbiotica strains.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results demonstrated that, once in the gut, cultivable S. symbiotica infections have negative effects on some A. fabae host life history traits in the absence of environmental stressors. These effects are similar to those found in previous studies that emphasize the costs associated with the presence of facultative endosymbionts for aphids, including the defensive endosymbiont Hamiltonella defensa (23,(27)(28)(29)(30)48). There may be several potential causes of virulence of cultivable S. symbiotica strains.…”
Section: Discussionsupporting
confidence: 86%
“…More erratically distributed in aphid populations than obligate partners, facultative partners are not essential for aphid host growth and reproduction but may lead to the acquisition of ecologically important traits by aphids (4,(23)(24)(25)(26). However, while facultative symbionts can have beneficial fitness consequences for aphid hosts, they can also impose a fitness cost on their host that makes them parasitic (22,(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…were also eliminated using microinjections of ampicillin (Leonardo, 2004;Sakurai et al, 2005;Simon et al, 2011), but this method failed to remove Hamiltonella defensa (Leonardo, 2004). One study also selectively eliminated S. symbiotica with ampicillin using an artificial medium supplemented with the antibiotic to feed A. pisum (Skaljac et al, 2018). Other methods using a cocktail of ampicillin, cefotaxime, and gentamicin instead of ampicillin solely allowed elimination of Fukatsuia symbiotica (also known as PAXS or Pea aphid X-type), H. defensa, R. insecticola, and S. symbiotica (Douglas et al, 2006;McLean et al, 2011;Simon et al, 2011) but failed to eliminate Rickettsia sp., Rickettsiella viridis, and Spiroplasma sp.…”
Section: Introductionmentioning
confidence: 99%
“…symbiotica ; Chen et al (2000); Mathé-Hubert et al (2019)), lower adult mass ( S . symbiotica; Skaljac et al (2018)), and increased susceptibility to insecticide ( S . symbiotica; Skaljac et al (2018)).…”
Section: Introductionmentioning
confidence: 99%
“…symbiotica; Skaljac et al (2018)), and increased susceptibility to insecticide ( S . symbiotica; Skaljac et al (2018)).…”
Section: Introductionmentioning
confidence: 99%